CAPACITY OF INVESTMENT IN HUMAN CAPITAL AND METHODOLOGY FOR MANAGEMENT SKILLS - Alvarado Daga, Guadalupe Esperanza (2013)
In a globalized world, the modern enterprise needs to go towards excellence, which means that you should be prepared to compete in quality with other companies in the same industry. It is important to consider human capital as a valuable asset in achieving this aim, for this we must equip them with the appropriate skills that are acquired through training competency considered as a continuous investment. The daily life of a company depends on it, by the influence of the performance of the activities in the processes that this human talent. The present work is a justification and a contribution to the management of human talent.